Oxytocin, its antagonist Atosiban, and preterm labor: a role for placental nitric oxide. (March 2015) - Nanetti, Laura; Raffaelli, Francesca; Giulietti, Alessia; Sforza, Giulia; Raffaele Giannubilo, Stefano; Ciavattini, Andrea; Tranquilli, Andrea Luigi; Mazzanti, Laura; Vignini, Arianna
Abstract Objective: The aim of the present study was to understand the role played by Atosiban, an oxytocin receptor antagonist, on trophoblastic human cells, and the molecular bases of its efficacy and safety in the treatment of preterm labor. NO, peroxinitrite production and NOS expression have been evaluated on placenta obtained from term and preterm labors. Patients and methods: We studied trophoblast cells isolated from selected placental tissue from 20 controls and 20 preterm patients after cesarean sections. Each sample was studied at basal state and after 2 hours incubation with oxytocin and Atosiban. Results: Significant variations of NO levels, peroxynitrite production and iNOS and eNOS expression both in the preterm, term samples and in each of the considered groups were observed. In the control group Atosiban re-established NO levels that were reduced after incubation with oxytocin, while in preterm samples NO levels were not only re-established but, after incubation with Atosiban, significantly increased compared to basal levels. Conclusions: This confirms the beneficial role of Atosiban in prolonging the pregnancy of spontaneous labor at very early gestational periods. In conclusion, Atosiban might be an effective drug to prevent preterm labor, in the therapeutic approach to this pathology.